Faith-Inspired Education in Ghana : A Historical Case Example - Olivier, Jill; Wodon, Quentin (Taylor and Francis, 2014)
In order to understand the current role of faith-inspired schools (FISs) in Africa and some of the debates about the magnitude of the services they provide, it is useful to consider their presence in a historical perspective. Faith-inspired schools have a long and distinguished tradition in sub-Saharan Africa. The purpose of this article is to sketch that history using the case of Ghana, a country where FISs date back to early Islamic schools and, as of the 16th century, to Christian missionary activities.